IMPLEMENTATION OF THE MINIMUM PRICE SETTING FOR FOREIGN PURCHASES BY FOREIGNERS - Putu Angga Pratama Sukma; Ni Putu Noni Suharyanti (International Journal of Applied Science and Sustainable Development (IJASSD), 2021)
Globalization has resulted in the increased mobility of foreigners to Indonesia. The foreigner has objectives such as investing, carrying out business needs, and carrying out tasks, then hierarchically and systematically based on the delegation of Law of the Republic of Indonesia Number 5 of 1960 Article 42 letter b to form Government Regulation of the Republic of Indonesia Number 103 of 2015. Substantive of this implementing regulation it will not be effective if it is seen from the substance of the validity of a mandatory norm, which means that its binding power is still appropriate and has been violated by foreigners and skeptically, this norm creates confusion in terms of practical implementation and in technical implementation in the form of deeds as the basis for There is an agreement when the form of deed required in connection with the extension of the ownership of a single house on land with usufructuary rights to the right of ownership is not clearly regulated so that the law cannot function the law to regulate changes.